PREPARATION OF ACYCLOVIR-ISONICOTINAMIDE COCRYSTAL BY SOLVENT EVAPORATION METHOD WITH METHANOL AND ISOPROPANOL - Agnes Nuniek Winantari; Roisah Nawatila; Cecilia Jocelyn (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2020)
PREPARATION OF ACYCLOVIR-ISONICOTINAMIDE COCRYSTAL BY SOLVENT EVAPORATION METHOD WITH METHANOL AND ISOPROPANOL. Acyclovir is a nucleoside synthetic analog antiviral group used in the treatment of Herpes simplex virus (HSV-1 & HSV-2) and Varicella zoster virus (VZV). Acyclovir has low water solubility, so it needs to be modified in the form of cocrystal with isonicotinamide. This study aims to obtain the physical characteristics produced by acyclovir-isonicotinamide cocrystal (1:1) made through the solvent evaporation method with methanol and isopropanol. The crystalline formed is characterized by DSC, PXRD, FT-IR and SEM. The characterization results showed the presence of new crystals that formed between acyclovir-isonicotinamide in methanol and isopropanol solvents. Thermograms showed sharp exothermic peaks at 183.31°C and 186.24°C. The diffractogram showed a new peak at 2θ = 5.19 and 5.82. The spectrum showed a shift in wavelength in the cocrystal formed. The cocrystal has a different morphology compared with parent drug and coformer on analysis using SEM. This research shows that acyclovir can form cocrystal with isonicotinamide by solvent evaporation method with methanol and isopropanol.